2021
DOI: 10.1007/s12471-021-01579-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antidiabetic agents on heart failure

Abstract: In the Netherlands, approximately 250,000 people are living with heart failure. About one-third of them have comorbid diabetes mellitus type 2. Until recently, the effects of antidiabetic agents on heart failure were largely unknown. This changed after an observed increased risk of heart failure and ischaemic heart disease associated with thiazolidinediones that prompted the requirement for cardiovascular outcome trials for new glucose-lowering drugs. In the past decade, three new classes of antidiabetic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Although, recent large randomized controlled trials have not shown differences in cardiovascular risk of sulfonylureas versus pioglitazone or linagliptin [70]. Some studies point to a higher incidence of DHF in patients with T2DM taking sulfonylureas; others show inconclusive data [71].…”
Section: Patients' Pharmacotherapeutic Profile and Acute Cardiovascul...mentioning
confidence: 99%
“…Although, recent large randomized controlled trials have not shown differences in cardiovascular risk of sulfonylureas versus pioglitazone or linagliptin [70]. Some studies point to a higher incidence of DHF in patients with T2DM taking sulfonylureas; others show inconclusive data [71].…”
Section: Patients' Pharmacotherapeutic Profile and Acute Cardiovascul...mentioning
confidence: 99%
“…Indeed, the insulin resistance observed in obese diabetic subjects directly impacts metabolic health through reduced systemic glucose clearance and progressive loss of lean muscle mass [2; 3]. Recent successes in glycemic control through antihyperglycemic drugs are positively impacting the management heart failure risk [4; 5]. However, muscle-centered mechanisms to rescue lean mass and strength in conditions of insulin resistance remain very limitedly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These trials mainly focus on 3-point major adverse cardiovascular events (3P-MACE) including CV death, nonfatal stroke, and nonfatal myocardial infarction (MI), with some including unstable angina (4P-MACE). In recent years, dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide-1 receptor agonists (GLP-1 RAs), and sodium-glucose cotransporter-2 inhibitors (SGLT2is) have emerged as newer classes of antidiabetic agents, undergoing extensive testing for their CV effects and demonstrating promising outcomes in reducing CV risks among individuals with T2DM [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%